Revealing organic carbon sources fueling a coral reef food web in the Gulf of Mexico using stable isotopes and fatty acids - Carreón-Palau, Laura; Parrish, Christopher C.; del Angel-Rodríguez, Jorge A.; Pérez-España, Horacio; Aguiñiga-García, Sergio (Limnology and oceanography, 2013)
Carbon and nitrogen stable isotopes and fatty acids (FAs) revealed primary producer organic carbon sources that fuel a coral reef food web with river influence. A stable isotope mixing model was used to assess the relative contribution of six different primary producers to nine of the most ubiquitous invertebrate and fish consumer’s bulk carbon. Mangrove and phytoplankton were difficult to differentiate in some consumers; likely solutions involved one or the other but not both at the same time. FA concentration in upper trophic levels was corrected for the primary producer’s relative contribution according to the mixing model, and FA retention was evaluated using a calculated trophic retention factor (TRF). The C18 FAs, 18:2ω6 and 18:3ω3, were plentiful in mangrove, sea grass, and green algae, but decreased across trophic levels with a TRF ≤ 1, probably due to decomposition of drifting leaves and then consumer metabolism. In contrast, macroalgae and phytoplankton FAs, 24:1ω9, and highly unsaturated fatty acids (HUFAs), arachidonic acid (ARA) 20:4ω6, docosapentanoic acid (DPA) 22:5ω3, and docosahexanoic acid (DHA) 22:6ω3, showed trophic accumulation (TRF > 1), while eicosapentanoic acid (EPA) 20:5ω3 had similar concentrations across trophic levels (TRF = 1), suggesting the following degrees of HUFA retention: DHA > ARA > EPA. This study indicates that phytoplankton are the major source of essential dietary nutrients for all fish, and that dietary energy from mangroves is transferred to juvenile fish Caranx hippos, while sea grass nonessential FAs are transferred to the entire food web. Moreover, among the species studied, the sea urchin Echinometra lucunter is the major consumer of brown and green algae, while red algae were also consumed by the surgeon fish Acanthurus chirurgus.